Pengobatan dengan Benda Haram dalam Persektif Islam - Mu’min Firmansyah; M. Hafiz Wijaya (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The aim of this research is to discuss the opinion that treatment with haram objects from an Islamic perspective causes controversy and debate. This article discusses how Islam views the use of haram objects in medicine and whether this is permissible or not. Based on several hadiths of the Prophet Muhammad, Islam places great emphasis on the importance of health and medical treatment, but also prioritizes halal principles and does not allow the use of haram objects as medicine. This article also discusses several different opinions of Islamic scholars in interpreting the law on the use of haram objects in medicine. In synthesis, this article shows that the use of haram objects in medicine is not permitted in Islam and that health must be achieved by means that are halal and in accordance with religious principles.